The assessment of cholinesterase from the blood of anabas testudineus as detection of metal ions - Muhammed Iqbal, Izzuanuddin (2015)
Climbing perch, or its scientific name, Anabas testudineus is one of the freshwater fishes that inhabit river areas. The fish belongs to the family Anabantidae and in Malaysia, its local name is “Ikan Puyu”. Cholinesterase (ChE) was partially purified from the blood extract of A. testudineus in this study through ion exchange chromatography with DEAE-Cellulose as column matrix. This method of purification provided recovery yield of 47.66% and purification fold of 8.37. Analysis of protein through Native polyacrylamide gel electrophoresis (Native-PAGE) proves that ChE had been successfully partially purified by ion exchange chromatography. Thus, ion exchange chromatography can be used as one of the purification methods to partially purify ChE from A. testudineus blood extract. The optimum conditions for ChE assay were identified to be at 30°C and pH 8.0 in phosphate buffer with 2 mM BTC as substrate. Metal ion inhibition study was conducted and it was found that mercury showed the highest inhibition effect (89.94%) on ChE activity. IC50 value of mercury towards the partially purified ChE was determined to be 1.733 ppm. These findings suggest that partially purified ChE from blood extract of A. testudineus is suitable to be used as bioindicator for the presence of metal ions in the environment.